The Rise and Fall of Brazil’s Science Without Borders - Sá Creso M (International Higher Education, 2016)
Brazil’s Science Without Borders, one of the largest efforts to promote student and researcher exchanges in recent years, has recently been suspended. This article examines several problems with policy design that cast doubt on the effectiveness of the program.